2021
DOI: 10.3390/cimb43030096
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of BCL6 and SIRT1 as Non-Invasive Diagnostic Markers of Endometriosis

Abstract: (1) Background: Endometriosis is characterized by the presence of endometrial glands and stroma outside of the uterus and is often associated with severe pelvic pain and infertility. Our study explored the utilization of B-Cell Lymphoma 6 (BCL6) and Sirtuin 1 (SIRT1) as potential biomarkers in serum, plasma, urine, and cervical mucus for a non-invasive diagnostic test for endometriosis. BCL6 was chosen based on its previously reported elevated expression in endometrial biopsies, and SIRT1 is co-expressed and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…A GC-like B-cell (FAS + IgD − BCL6 + ) population was also identified, representing 12.2 ± 8.6% of all endometrial B cells. Previous studies demonstrated that endometrial B-cell lymphoma-6 (BCL6) protein levels are significantly higher in patients with RPL, unexplained infertility or endometriosis (eutopic endometrium) when compared with controls ( Evans-Hoeker et al , 2016 ; Almquist et al , 2017 ; Fox et al , 2020 ; Sansone et al , 2021 ). However, BCL6 expression is not limited to endometrial B cells, therefore, it is not yet clear whether the up-regulation of BCL6 is a reflection of the existence and/or involvement of GC-like B cells in the endometrial environment.…”
Section: Discussionmentioning
confidence: 99%
“…A GC-like B-cell (FAS + IgD − BCL6 + ) population was also identified, representing 12.2 ± 8.6% of all endometrial B cells. Previous studies demonstrated that endometrial B-cell lymphoma-6 (BCL6) protein levels are significantly higher in patients with RPL, unexplained infertility or endometriosis (eutopic endometrium) when compared with controls ( Evans-Hoeker et al , 2016 ; Almquist et al , 2017 ; Fox et al , 2020 ; Sansone et al , 2021 ). However, BCL6 expression is not limited to endometrial B cells, therefore, it is not yet clear whether the up-regulation of BCL6 is a reflection of the existence and/or involvement of GC-like B cells in the endometrial environment.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of the gene encoding transcriptional repressor BCL6 (B-cell lymphoma 6) in the endometrium allows the detection of endometritis associated with endometriosis [ 161 ]. Elevated BCL6 and aromatase levels are associated with progesterone resistance and estrogen dominance in women with endometriosis [ 129 ].…”
Section: Inflammation-related Molecules In Pathologically Altered End...mentioning
confidence: 99%
“…Initially described as a proto-oncogene and transcriptional repressor implicated in the pathogenesis of B-cell lymphoma, BCL6 has recently been identified as a promising tissular biomarker which could be used to diagnose women affected by endometriosis [ 1 , 2 , 3 , 4 ]. The recent identification of actors acting in conjunction with BCL6, and the delineation of several target genes have helped to better determine its biological functions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…While alternative methods such as medical imaging, genetic tests, or biomarkers are aimed at alleviating invasive diagnosis, none of them can adequately substitute for surgery at present [ 23 , 24 , 25 , 26 , 27 ]. Recent studies have identified a promising tissular biomarker called B-cell lymphoma 6 (BCL6), which could be used to diagnose women affected by endometriosis [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation